HEALTH INSURANCE: IDENTIFYING AWARENESS, PREFERENCES AND BUYING PATTERN IN MUMBAI (International Journal of Food and Nutritional Sciences, 2022)
When it comes to insurance, the Covid-19 pandemic has been a major game changer. The severe impact of the pandemic has changed the perception about insurance as the need for the financial back up was felt to meet unforeseen medical emergencies. It was an eye opener even for the young generation as they are exposed to much higher health risk due to fast changing life styles and increasing stress levels. A holistic health insurance plan became necessary to ensure the safety and wellbeing of the loved ones in times of distress. Health insurance in India is a growing segment of economy. By 2025, the Government of India is planning to increase public health spending to 2.5 per cent of the country's GDP. Although the demand for health insurance has increased considerably but still there is a sizeable section of society in India not yet covered by any health insurance scheme.The present paper is an attempt to study people’s awareness, perception and preferences towards health Insurance. The study aims to determine whether health insurance plans are fulfilling the needs of the society and to examine the factors taken into consideration while opting Health insurance policy.The study is based on the information gathered from the Primary and Secondary sources. Primary data is collected with the help of well-designed questionnaire from respondents from Mumbai city and secondary data consists of information collected through various websites, newspapers and articles.